Radical-type Reactions Controlled by Cobalt: From Carbene Radical Reactivity to the Catalytic Intermediacy of Reactive o-Quinodimethanes - te Grotenhuis, Colet; de Bruin, Bas (Synlett, 2018)
In this account, we summarize our recent efforts in the fields of ‘open-shell organometallic chemistry’ and ‘metalloradical catalysis’. We focus in particular on the use of so-called ‘carbene radicals’ for the synthesis of a variety of useful synthons for organic chemistry. We further show that unexpected reactivity arises from catalytic synthesis of unusual o-quinone methide and o-quinodimethane intermediates that undergo subsequent rearrangements to uncommon products.1 Introduction2 General (Fischer-Type) Carbene and Nitrene Reactivity and Their Relation to Carbene and Nitrene Radical Reactivity3 Carbene and Nitrene (Radical) Precursors4 Formation and Intrinsic Radical-Type Reactivity of Carbene and Nitrene Radicals5 Types of Cobalt Catalysts Used in Reactions Involving Carbene and Nitrene Radicals6 Applications of Cobalt-Catalyzed Ring-Closure Reactions via Carbene Radicals7 Intermediacy of o-Quinone Methide and o-Quidodimethanes in Carbene Ring-Closing Reactions8 Conclusion
Keywords: carbene radicals; carbene reactivity; metalloradical catalysis; o-quinodimethanes; open-shell organometallic chemistry